2021
DOI: 10.1159/000515633
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hippo Signaling Pathway in the Development of the Nervous System

Abstract: Hippo signaling pathway is a highly conserved and crucial signaling pathway that controls the size of tissues and organs by regulating the proliferation, differentiation, and apoptosis of cells. The nervous system is a complicated system that participates in information collection, integration, and procession. The balance of various aspects of the nervous system is vital for the normal regulation of physiological conditions of the body, like the population and distribution of nerve cells, nerve connections, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Strikingly, all those conditions caused by NUP205 mutations are related with YAP/TAZ expression. [61][62][63][64][65][66][67][68] In conclusion, our findings highlight the important role of YAP/TAZ signaling in podocyte homeostasis by connecting the shuttling of YAP and TAZ to a nucleoporin, known to cause which highlights new specific therapeutic targets for FSGS like stabilizing nuclear YAP activity in podocytes.…”
Section: Discussionmentioning
confidence: 59%
“…Strikingly, all those conditions caused by NUP205 mutations are related with YAP/TAZ expression. [61][62][63][64][65][66][67][68] In conclusion, our findings highlight the important role of YAP/TAZ signaling in podocyte homeostasis by connecting the shuttling of YAP and TAZ to a nucleoporin, known to cause which highlights new specific therapeutic targets for FSGS like stabilizing nuclear YAP activity in podocytes.…”
Section: Discussionmentioning
confidence: 59%
“…Our analysis revealed that Gm10545, Gm16096, Gm29260, and Mir100 hg were involved in mannose-type O -glycan biosynthesis, providing a mechanism by which m 6 A-methylated DElncRNAs affected the development of NTDs. Moreover, A730017L22Rik, Gm19265, and Gm5165 were implicated in the Hippo signaling pathway, which has established roles in neuronal cell differentiation, neuroinflammation, and neuronal death ( Cheng et al, 2020 ; Li X. et al, 2021 ). The Hippo/YAP signaling pathway has been implicated in the development of neurological diseases ( Bao et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Hippo signaling pathway regulates overall organ size in several systems [ 41 ]. In the brain, it regulates the size of the cortical hem, progenitor proliferation, basal progenitor expansion, synaptic development, corpus callosum formation, and astrocyte differentiation [ 42 , 43 ]. Many of these functions overlap with those reported for Lhx2 .…”
Section: Discussionmentioning
confidence: 99%